Phytochemical profiling of Turbinaria ornata and its antioxidant and anti-proliferative effects. Issue 4 (August 2017) - Deepak, Paramasivam; Sowmiya, Rajamani; Balasubramani, Govindasamy; Perumal, Pachiappan
الملخص: أهداف البحث: لتحليل المواد الكيميائية النباتية، وتقييم القدرات المضادة للأكسدة والمضادة للتكاثر لـ "تربيناريا أورناتا" ( ترنر) أجارد ١٨٤٨. طرق البحث: أجريت التحاليل الكيميائية النباتية للمستخلص الهكساني، والمستخلص المائي لـ "تربيناريا أورناتا". تم تحليل المستخلصات باستخدام تقنيات؛ الطيف الكتلي اللوني للغاز، وجهاز "فورييه" للتحويل الطيفي للأشعة تحت الحمراء، وفاصل الألوان السائل عالي الكفاءة. تم تحديد الخاصية المضادة للأكسدة للمستخلص الهكساني والمستخلص المائي لـ "تربيناريا أورناتا" باستخدام فحص بكرايل هايدرزايل ثنائي الفينايل للكسح الجذري وفحص قوة اختزال أيون الحديديك. بالإضافة إلى ذلك تم تقييم الخاصية المضادة للتكاثر داخل الخلية على الخلايا الظهارية الكلوية للقرد الأفريقي الأخضر (فيرو)، والخلايا الظهارية القاعدية السنخية البشرية السرطانية باستخدام فحص إم تي تي. النتائج: كشف الفحص الكيميائي النباتي لـ "تربيناريا أورناتا" وجود سابونين، وقلويدات وأحماض أمينية، وزيت ودهن ثابتين، ومركبات فينولية (العفص وفلافونيدات والفينول الكلي). وجدت الخاصية المضادة للتكاثر الأعلى في المستخلص الهكساني ويليها المستخلص المائي لـ "تربيناريا أورناتا". كانت قيم فعالية مكافحة التكاثر (بالـ مايكروجرام/ مليلتر) بالنسبة للمستخلص الهكساني والمستخلص المائي على الخلايا الظهارية القاعدية السنخية البشرية السرطانية وخلايا فيرو: ٦٢٬٩١ و٩٣٬٠٠ و٧٢٬٦٤ و١٠٦٬٦ على التوالي. وقد أظهر التحليل باستخدام جهاز "فورييه" للتحويل الطيفي للأشعة تحت الحمراء وجود مجموعات وظيفية هي: الكحول، الأميدات والعطريات، والأمينات، وهاليدات الألكيل، والألكاينات، والألكانات، والأحماض الكربوكسيلية. كما كشف الطيف الكتلي اللوني للغاز عند تحليل المستخلص الهكساني لـ "تربيناريا أورناتا" عن وجود ١٣ مركبا نشطا. الاستنتاجات: بناء على الخاصية المضادة للتكاثر المسجلة فإن هناك حاجة للمزيد من الدراسات الدوائية في سبيل تحضير دواء مضاد للسرطان. Abstract: Objectives: To analyse the phytochemicals and evaluate the antioxidant and anti-proliferative ability of Turbinaria ornata (Turner) J. Agardh, 1848. Methods: A phytochemical analysis of the T. ornata -hexane extract (To-HE) and T. ornata -aqueous extract (To-AE) was performed. T. ornata extracts were analysed by gas chromatography-mass spectrometry (GC-MS), Fourier transform infrared spectroscopy (FTIR) and high-performance liquid chromatography (HPLC). The antioxidant properties of To-HE and To-AE were determined by 2, 2-diphenyl-1-picrylhydrazyl radical scavenging (DPPH) and ferric ion reducing power (FRAP) assays. In addition, the in vitro anti-proliferative properties of To-HE and To-AE were assessed in kidney epithelial cells from the African green monkey ( Vero ) and in adenocarcinomic human alveolar basal epithelial cells (A549) using the MTT (3-(4, 5-dimethylthiazol- 2yl)-2, 5-diphenyltetrazolium bromide, a yellow tetrazole) assay. Results: The phytochemical screening of T. ornata revealed the presence of saponin, alkaloids, amino acids, fixed oil and fat and phenolic compounds (tannins, flavonoids and total phenol). A higher antioxidant ability was found in To-HE than in To-AE. The anti-proliferative efficacy values (μg/mL) of To-HE and To-AE for A549 and Vero cells were 62.91 and 93.00 and 72.64 and 106.6, respectively. The FTIR analysis revealed the presence of functional groups such as alcohols, amides, aromatics, amines, alkyl halides, alkynes, alkanes and carboxylic acids. The GC-MS analysis of To-HE revealed the presence of 13 active compounds. Conclusion: Owing to its recorded anti-proliferative effect, further pharmaceutical studies on the development of this anticancer drug are merited.